La variante en el Romancero manuscrito e impreso del siglo XVI: pautas en la corrección de copistas, impresores y autores - Higashi, Alejandro (El Colegio de México, 2013)
The review of some of the strategies of variation in the sixteenth centuryRomances shows that these were spread among various actors involved in the processes of production and transmission of ballads, from the author himself and even compilers, printers and other intermediaries;the collective nature of this intervention reduces the interest to distinguish between author’s variants and compiler’s variants,printer’s variants, etc. This kind of variation in the Romancero, regardless their origins, follows a similar pattern (concerning lexical, syntagmatic, stichomytic and prosodic axes, limits on the involvement into the narrative structure), expossing some common prejudices as the aesthetic superiority of author’s variants vs. non-author’s variants,in a creative process where the key seems to be on collaboration ratherthan on the independent genius of an author.